AMNIOTIC MEMBRANE TRANSPLANT AS ADJUVANT THERAPY FOR SEVERE INFECTIOUS CORNEAL ULCER: Poster Presentation - Case Report - General practitioner - Yulis Kristanto (Majalah Oftalmologi Indonesia, 2023)
Introduction : Infectious corneal ulcer may lead to visual impairment and contribute to five percent of blindness worldwide. Amniotic membrane transplant is one of adjuvant therapies listed to aid in the management of corneal ulcer. Case Illustration : There were two cases of severe corneal ulcer, both patients had exposure from vegetative matter. Case 1: A 40 years old male came with decreased VA in left eye (VA OS 1/300) and VAS 4, corneal epithelial stromal defect measuring 3x5 mm with 2 mm hypopyon. After three days of inpatient management, AMT procedure was done followed by temporary tarsorrhaphy. On 14th day of observation, tarsorrhaphy was removed, VAS was decreased to 0 and hypopyon resolved. On 28th day, corneal leukoma was observed with visual acuity improved (VA OS 1/60). Case 2: A 63 years old female came with decreased visual acuity (VA OD 1/300), followed by VAS 4, epithelial stromal defect measuring 7.3x5.4 mm, and 1 mm hypopyon. AMT procedure was done in fourth day of hospitalization. On seventh day, VAS was reduced to 1-2. On 14th day, tarsorrhaphy was removed, corneal leukoma was observed and on 28th day of observation, visual acuity was improved (VA OD 6/21). Discussion : AMT may induce faster regeneration of wound healing, as it halts inflammation, fibrosis, angiogenesis, and protease activities. AMT also increases the stromal thickness, as the membrane becomes incorporated into the stroma. By placing a temporary tarsorrhaphy, it may promote healing further into the corneal defects. Conclusion : AMT is effective in promoting epithelialization and preventing corneal perforations in corneal ulcers.